The influence of ENSO and rainfall on the numbers of breeding pairs in a woodland bird community from south-eastern Australia. (1st September 2016) - Marchant, R.; Guppy, S.; Guppy, M.
Abstract: Climate and rainfall in southern Australia are strongly influenced by the El Nino-Southern Oscillation (ENSO) phenomenon. If breeding of forest birds is related to rainfall, then ENSO may influence fluctuations in breeding activity. We recorded the numbers of breeding pairs of 17 species over 17 years on a 10 ha forest plot near Moruya, NSW, in order to evaluate the influence of ENSO (as measured by the Southern Oscillation Index, SOI) and rainfall on yearly changes in breeding activity. The mean SOI for the months April-July immediately before the breeding season (August-January) was strongly correlated with the change in number of breeding pairs (D) from year to year: r = 0.82, P <0.001.D was also strongly correlated with rainfall (August to December) during breeding: r =0.84, P <0.001. A positive SOI resulted in >300mm rainfall during breeding and a positive D value; a negative SOI resulted in <300 mm of rain and a negative D value. SOI was a better predictor because it was less subject to the extreme variation shown by rainfall. This is the first time an association between breeding and SOI has been shown for forest birds in temperate Australia.